Youth Narratives of Moderate Islam: Study of Islamic Philosophy For Indonesian Millennials - Kanafi, Imam; Bakhri, Syamsul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study examines the Islamic narratives faced by the Muslim millennial generation in Indonesia, a group often targeted by radical groups. Using a phenomenological approach in qualitative research, data were collected through in-depth interviews and media content analysis involving 30 millennial participants from various backgrounds, including Islamic boarding school students and social media users. This study focuses on three aspects: sources of Islamic narratives, understandings of moderation and ideal Muslim figures, and responses to moderate Islamic narratives. The study revealed a broad spectrum of Islamic narratives, ranging from radical to moderate, shaped by sources such as Islamic boarding schools, teachers, prayer groups, books, and social media. Indonesian Muslim millennials showed a strong preference for moderate Islamic leaders over Salafi figures, reflecting the appeal of narratives that promote tolerance and Pancasila values. The majority of millennials support the spread of moderate Islamic values despite exposure to a variety of narratives. This study contributes to academic discourse by providing insights into the interaction of digital media, religious education, and the formation of Islamic identity. Methodologically, this study demonstrates the effectiveness of combining phenomenological analysis and digital ethnography to understand contemporary religious narratives. These findings are relevant in designing strategies to counter radicalism and strengthen the narrative of moderate Islam in pluralistic societies.